The Role of Gratitude and Perceived Social Support on Teacher Subjective Well-Being During the Pandemic - Ahmad M. Mahasneh; Juan Hernández-Lalinde; María Luisa Martínez-Martí (Tinta Emas Publisher, 2024)
This study aims to analyze the effect of perceived social support and gratitude on teacher subjective well-being of honorary teachers in secondary schools in Madrid during the pandemic. Using a quantitative approach with an ex post facto design, this study involved 202 honorary teachers selected through purposive sampling. The research instruments included the Gratitude Questionnaire, the Revised-Multidimensional Scale of Perceived Social Support (R-MSPSS), and the Teacher Subjective Well-Being Questionnaire (TSWQ). The results of the analysis using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) showed that perceived social support and gratitude played a significant and positive role in teacher subjective well-being. The higher the perceived social support and gratitude values, the higher the level of teacher subjective well-being. The results of this study have theoretical implications for the development of educational psychology and positive psychology, as well as providing practical recommendations for teachers and the government to improve teacher well-being through curriculum adaptation and other supporting strategies.